2021
DOI: 10.3389/fcimb.2021.678231
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphism in Neopseudocercosporella capsellae, an Emerging Pathogen Causing White Leaf Spot Disease of Brassicas

Abstract: White leaf spot pathogen: Neopseudocercosporella capsellae causes significant damage to many economically important Brassicaceae crops, including oilseed rape through foliar, stem, and pod lesions under cool and wet conditions. A lack of information on critical aspects of the pathogen’s life cycle limits the development of effective control measures. The presence of single-celled spores along with multi-celled conidia on cotyledons inoculated with multi-celled conidia suggested that the multi-celled conidia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Recently, N . capsellae was shown to have significant morphological plasticity that enables it to transform from multicelled conidia to the single‐celled yeast‐like phase depending upon the external stimuli (Gunasinghe et al, 2021), and this probably plays an important role in host invasion in relation to defining virulence of the pathogen, as shown in other studies by Lin et al (2014) for Ophiostoma ulmi , the causal organism of Dutch elm disease, and by Mehrabi et al (2006) for the fungal wheat pathogen Mycosphaerella graminicola . Likewise, Singh et al (2002) reported that preinoculation of B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, N . capsellae was shown to have significant morphological plasticity that enables it to transform from multicelled conidia to the single‐celled yeast‐like phase depending upon the external stimuli (Gunasinghe et al, 2021), and this probably plays an important role in host invasion in relation to defining virulence of the pathogen, as shown in other studies by Lin et al (2014) for Ophiostoma ulmi , the causal organism of Dutch elm disease, and by Mehrabi et al (2006) for the fungal wheat pathogen Mycosphaerella graminicola . Likewise, Singh et al (2002) reported that preinoculation of B .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, N. capsellae was shown to have significant morphological plasticity that enables it to transform from multicelled conidia to the single-celled yeast-like phase depending upon the external stimuli (Gunasinghe et al, 2021), and this probably plays an important role in host invasion in relation to defining virulence of the pathogen, as…”
Section: Discussionmentioning
confidence: 99%